Epidemiological and molecular survey of a foodborne disease outbreak caused by Enterococcus faecalis - Xiawei CHEN; Chunsheng CAI; Binhong HE; Shunshan CAO; Yan GUO; Yuekang ZHENG; Jinjie OU; Boyuan WANG (Zhongguo shipin weisheng zazhi, 2020)
Objective To investigate a foodborne disease outbreak in a small restaurant, analyze its causes and risk factors, and propose the measures for prevention and control. Methods Using field epidemiology survey to describe the features and analyze the risk factors of the incident. The strains homology was evaluated by pulsed field gel electrophoresis (PFGE). Results The major clinic manifestations of 5 cases were diarrhea and abdominal pain. Dietary survey showed that suspicious food was pot-stewed chicken leg at dinner on June 13, 2019. The result of field hygienic survey indicated that the risk factor of the incident was the long placement time of the pot-stewed chicken leg at normal temperature status and insufficient re-heating time before dinner. Enterococcus faecalis was isolated from 3 anal swabs of cases, the pot-stewed chicken leg and the cutting board swab which sampled in the kitchen, and the strains were 100% homological. Conclusion The outbreak was caused by eating the pot-stewed chicken leg which was contaminated by abundant Enterococcus faecalis. It was suggested to strengthen the food safety awareness of small restaurant employees and the proper cooking method should be mastered.